2015
DOI: 10.1016/j.ssresearch.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Family and housing instability: Longitudinal impact on adolescent emotional and behavioral well-being

Abstract: This study investigated the longitudinal effects of family structure changes and housing instability in adolescence on functioning in the transition to adulthood. A model examined the influence of household composition changes and mobility in context of ethnic differences and sociodemographic risks. Data from the National Longitudinal Study of Adolescent Health measured household and residential changes over a 12-month period among a nationally representative sample of adolescents. Assessments in young adultho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 67 publications
6
62
1
Order By: Relevance
“…Moreover, the social psychology literature suggests that it may be particularly costly to move children during adolescence, when social bonds are strongest and thus the potential for social disruption is greatest (e.g. Fowler, Henry, & Marcal, 2014 and 2015), and this period roughly coincides with secondary school attendance (hereafter “high school” as it is called in the U.S.). As such, our analyses will examine how both the number and age of children influences scientist mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the social psychology literature suggests that it may be particularly costly to move children during adolescence, when social bonds are strongest and thus the potential for social disruption is greatest (e.g. Fowler, Henry, & Marcal, 2014 and 2015), and this period roughly coincides with secondary school attendance (hereafter “high school” as it is called in the U.S.). As such, our analyses will examine how both the number and age of children influences scientist mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we expect that mothers’ employment status and changes in that status play a significant role in shaping when and how parents and children interact. Prior research has demonstrated that instability in each of these domains is predictive of children’s behavior problems and diminished school readiness (Cooper et al 2011; Fomby and Cherlin 2007; Fowler et al 2015; Mollborn et al 2012; Morrissey 2009; Rege et al 2011), but little research to date has considered the extent to which transitions in these various domains co-occur or whether closely sequenced transitions across multiple domains are distinctively associated with children’s subsequent development compared to transitions in a single domain (Crosnoe et al 2014; Fomby and Sennott 2013; Fowler et al 2015; South, Crowder and Trent 1998). …”
Section: Children’s Developmental Ecologiesmentioning
confidence: 99%
“…Broadly, instability has been defined as frequent and closely sequenced changes in the composition and characteristics of children’s social contexts. Much work has focused on instability in specific domains, including parents’ union instability (Cavanagh and Huston 2006; Fomby and Cherlin 2007; Lee and McLanahan 2015; Osborne and McLanahan 2007; Wu and Martinson 1993), changes in coresidence with extended kin (Dunifon and Kowaleski-Jones 2007; Landale, Oropesa and Noah 2014; Mollborn et al 2012), residential mobility (Fomby and Sennott 2013; Fowler et al 2015; Haynie et al 2006; South et al 2005), parents’ variable work schedules and employment status (Conger and Elder 1994; Dunifon et al 2013; Rege et al 2011), and frequent changes in child care arrangements (Crosnoe et al 2014). More recently, scholars have drawn on the concept of environmental chaos to consider whether child well-being is compromised by the “routine uncertainty” that emerges from experiencing frequent change in a variety of domains simultaneously or in close sequence (Coley et al 2015; Kamp Dush et al 2013; Odgers and Jaffee 2013; Vernon-Feagans et al 2016).…”
mentioning
confidence: 99%
“…Prior work suggests mobile adolescents express higher rates of depression than their stable peers in analyses using data from the National Longitudinal Study of Adolescent Health (Add Health; Fowler, Henry, & Marcal, 2015;Haynie & South, 2005). Data from the NICHD Study of Early Child Care and Youth Development (NICHD SECCYD), suggests mobile adolescents experienced significantly greater internalizing behavior when compared to stable adolescents but only marginally for externalizing behaviors (Anderson et al, 2014a).…”
Section: Residential Mobility In Adolescencementioning
confidence: 99%
“…Prior research concerning residentially mobile adolescents has also considered the delinquent outcomes of those who move compared to those who do not. Researchers examining the frequency of adolescent arrests using data from the National Longitudinal Study of Adolescent Health (Add Health) found residentially mobile adolescents were more likely to be arrested than their stable peers (Fowler et al, 2015). A study using NLSY79 data found residentially mobile adolescents reported significantly higher levels of involvement in violence than stable adolescents (Haynie & South, 2005;Gillespie, 2013).…”
Section: Residential Mobility In Adolescencementioning
confidence: 99%